C reactive protein concentrations during long distance running. Issue 6454 (10th November 1984) - Strachan, A F; Noakes, T D; Kotzenberg, G; Nel, A E; de Beer, F C
Abstract : Long distance runners competing in events ranging from 15 to 88 km showed a distance related acute phase response as indicated by significantly raised serum C reactive protein concentrations. In trained athletes only a small rise in C reactive protein concentrations was seen after races of less than 21 km. After an 88 km ultramarathon concentrations comparable to those found in patients with small myocardial infarctions were detected. Indomethacin did not affect the increases in C reactive protein after the ultramarathon. This study has established serial C reactive protein concentrations for given race distances. These data may help in diagnosing myocardial infarction during long distance running. The acute phase response should be measured in untrained people running shorter distances to provide comparative data for the physically untrained population.